Pengawasan dan Pemberdayaan Wakaf di Indonesia - Latifatul Azizah; Desy Kusuma Wardhani, M. Alif Fianto, Zulham Mahmudin (Laboratorium Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2021)
Abstract: Waqf is a legal act of wakif to separate and surrender part of his property forever or for a certain period by his interests for appropriate worship and public purposes. In its implementation, there is supervision and empowerment of Waqf, whose provisions are regulated in Law no. 41 of 2004 concerning Waqf. The minister carries out the guidance and care of Waqf by taking into account the suggestions and considerations of the Indonesian Ulema Council. In addition, waqf supervision is also carried out by the community and the government. The Indonesian Waqf Board (BWI) was formed to develop and advance Waqf in Indonesia. BWI is an independent state institution established based on Law Number 41 of 2004 concerning Waqf. In empowering Waqf in Indonesia, waqf empowerment institutions must establish cooperation or partnerships with various parties who have capital and business interests by waqf objects with high commercial value, not only with the State Budget and Expenditure Revenue Government (APBN). In this case, business partnership relationships are needed, as well as third parties and other institutions that support waqf management. Keywords: Waqf, Supervision and Empowerment Abstrak: Wakaf ialah perbuatan hukum wakif untuk memisahkan dan/atau menyerahkan sebagian harta benda miliknya untuk dimanfaatkan selamanya atau untuk jangka waktu tertentu sesuai dengan kepentingannya guna keperluan ibadah dan/atau kesejahteraan umum sesuai Syariah. Dalam implementasinya terdapat pengawasan dan pemberdayaan wakaf yang ketentuannya diatur dalam Undang-Undang No. 41 Tahun 2004 tentang Wakaf. Pembinaan dan pengawasan wakaf dilakukan oleh menteri dengan memperhatikan saran dan pertimbangan Majelis Ulama Indonesia. Selain itu pengawasan wakaf juga dilakukan leh masyarakat dan pemerintah. Untuk mengembangkan dan memajukan perwakafan di Indonesia maka dibentuk Badan Wakaf Indonesia (BWI). BWI adalah lembaga negara independen yang dibentuk berdasarkan Undang-Undang Nomor 41 Tahun 2004 tentang Wakaf. Dalam pemberdayaan wakaf di Indonesia, Lembaga-lembaga pemberdayaan wakaf harus menjalin kerjasama atau kemitraan dengan berbagai pihak yang mempunyai modal dan ketertarikan usaha sesuai dengan benda wakaf yang ada dengan nilai komersial yang tinggi sehingga tidak bergantung saja dengan Anggaran Pendapatan dan Belanja Negara (APBN) dari pemerintah. Dalam hal ini dibutuhkan hubungan kemitraan usaha, mitra usaha sebagai pihak ketiga dan lembaga lain yang mendukung pengelolaan wakaf. Kata kunci:. Wakaf, Pengawasan, Pemberdayaan.